Ectopic expression of the cowpea (Vigna unguiculata) VuCERK1 gene confers enhanced resistance to Pto DC3000 hrcC- in Arabidopsis - Weida Chen; Lifen Gao; Gao Chen; Ting Yang; Zixin Zhao; Wenhao Xia; Niannian Fan; Siming Chen (Czech Journal of Genetics and Plant Breeding)
Pattern recognition receptors (PRRs) play multiple roles in plants. As a kind of PRRs, chitin elicitor receptor kinase 1 (CERK1) proteins were reported to function in plant resistance to fungal and bacterial pathogens, and tolerance to salt stress. In this study, a predicted cowpea CERK1 homologous gene, designated as VuCERK1, was identified by database search. VuCERK1 protein contains 618 amino acid residues, with a predicted molecular mass of 67.5 kDa and a predicted isoelectric point of 5.04. VuCERK1 shows 58% and 60% sequence identity with AtCERK1 and OsCERK1, respectively. VuCERK1 also shows similar subcellular pattern with AtCERK1 and OsCERK1, suggesting VuCERK1 may function in cowpea immune responses. Gene expression assay indicated, that VuCERK1 was expressed in four different seedling tissues tested, comprising first leave, epicotyl, hypocotyl and root, and it could be induced by salt stress. Furthermore, transient expression of VuCERK1 in Nicotiana benthamiana induced obvious cell death. In addition, heterologous overexpression of VuCERK1 in Arabidopsis thaliana conferred enhanced disease resistance to Pseudomonas syringae pv. tomato strain DC3000 hrcC- (Pto DC3000 hrcC-).